UPAYA KOMISI PEMILIHAN UMUM (KPU) DALAM MENINGKATKAN PARTISIPASI POLITIK PEMILIH PEMULA PADA PEMILIHAN GUBERNUR DAN WAKIL GUBERNUR, BUPATI DAN WAKIL BUPATI KABUPATEN PASAMAN BARAT DI NAGARI SITUAK UJUNG GADING KECAMATAN LEMBAH MELINTANG KABUPATEN PASAMAN BARAT TAHUN 2024 - Siska Marlina; Rofah Rofah (Ensiklopedia of Journal, 2026)
This study addresses the issue of low political participation among first-time voters in the 2024 regional elections in West Pasaman Regency. The objective of the study was to analyze the efforts of the West Pasaman Regency General Elections Commission (KPU) to increase first-time voter participation and identify the obstacles faced, particularly in Situak Ujung Gading Village, Lembah Melintang District. The method used was qualitative with a descriptive approach through interviews and observations. The results showed that the KPU (General Elections Commission) had implemented various voter education and outreach initiatives. However, participation was still hampered by low political knowledge among first-time voters, ineffective outreach, and minimal awareness of obtaining a National Identity Card (KTP) as an administrative requirement for voters in the ongoing local democratic process.Keywords: General Election Commission (KPU), Political Participation and New Voters